The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00381-004-1091-3
|View full text |Cite
|
Sign up to set email alerts
|

Dumbbell trigeminal schwannoma in a child: complete removal by a one-stage pterional surgical approach

Abstract: Trigeminal schwannoma is a tumour that occurs rarely in childhood. Although several, often multistaged surgical strategies have been reported in the literature, this tumour was eradicated by a one-stage pterional approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…The subarachnoid space extends forward within Meckel's cave to approximately the midportion of the gasserian ganglion. Disruption in Meckel's cave may lead to various abnormalities, among which trigeminal schwannomas (TS) and meningiomas are the most common [2][3][4] . Many surgical approaches to the lesions in Meckel's cave have been reported [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The subarachnoid space extends forward within Meckel's cave to approximately the midportion of the gasserian ganglion. Disruption in Meckel's cave may lead to various abnormalities, among which trigeminal schwannomas (TS) and meningiomas are the most common [2][3][4] . Many surgical approaches to the lesions in Meckel's cave have been reported [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although very few pediatric cases of trigeminal schwannomas have been reported in the literature, 3,4 to our knowledge, this is the first case of an atypical meningioma along the trigeminal nerve in a pediatric patient.…”
Section: Discussionmentioning
confidence: 80%
“…Major impediment to complete removal is inadequate exposure due to deep location of the tumor and close proximity to vital neuro-vascular structures. The ideal surgical approach should be shortest and direct as well as wide and low so as to avoid the need for prolonged and excessive brain retraction.Verstappen et al [11] reported a case of trigeminal neurinoma of maximum diameter of 53mm, centered over Meckel , s cave in a 6 year old girl removed by single stage pterional approach. However with pterional approach it is difficult to remove large posterior fossa component as was in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor that straddle the middle and posterior cranial fossae and do not extend below the internal auditory canal can be removed through a middle fossa approach [2,11]. The combined approach is employed for large dumbbell shaped tumors that extend ventral to the lower brainstem and below the internal acoustic meatus [2,11]. Various reports have stressed the need for radical surgery so as to achieve higher cure rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation